PENGARUH KEPEMIMPINAN ETIS DAN KOMUNIKASI INTERNAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT MULTI CITRA RASA KOTA TANGERANG - Zihan Adhelia Sahila; Andri Priadi (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to determine the influence of ethical leadership and internal communication on employee work productivity at PT Multi Citra Rasa, Tangerang City. The study used a quantitative method with an associative approach. The population consisted of 250 employees, and 72 respondents were selected using the Slovin formula with a 10% error rate and proportional random sampling. Data were analyzed using SPSS version 26 through validity and reliability tests, classical assumption tests, correlation, coefficient of determination, simple and multiple linear regression, t-tests, and an F-test. Ethical leadership had a significant effect on work productivity (t = 7.585; p < 0.001), and internal communication also had a significant effect (t = 17.501; p < 0.001). Simultaneously, ethical leadership and internal communication significantly affected work productivity (F = 151.222; p < 0.001). The multiple regression equation was Y = 6.958 + 0.739X1 + 0.849X2, with R² = 0.814.